2017
DOI: 10.1111/jora.12358
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Externalizing Problems: Contributions of Community Crime Exposure and Neural Function During Emotion Introspection in Mexican‐Origin Youth

Abstract: Models of the etiology of adolescent antisocial behavior suggest that externalizing problems may reflect a susceptibility to crime exposure and a diminished capacity for emotion introspection. In this study, adolescents of Mexican origin completed a neuroimaging task that involved rating their subjective feelings of sadness in response to emotional facial expressions or a nonemotional aspect of each face. At lower levels of neural activity during sadness introspection in posterior cingulate and left temporopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 57 publications
0
16
0
2
Order By: Relevance
“…Using a region of interest (ROI) approach, we have shown that dorsomedial (dmPFC) activity during sadness introspection when viewing sad faces was related to depression severity 1 year later and to self‐reported emotion regulation (Vilgis et al, ). We have also found that stronger activation of social–emotional processing regions (i.e., the PCC, left TPJ, and left amygdala) during sadness introspection, regardless of facial expression, moderated the relation between community crime exposure and disruptive behavior problems (Weissman et al, ). In accordance with this previous research, our first hypothesis of the present study was that engaging in sadness introspection (explicit emotion processing) would induce specific patterns of neural activity in social–emotional processing and DMN regions, including mPFC, precuneus, and temporal regions, similar to what other studies have shown.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Using a region of interest (ROI) approach, we have shown that dorsomedial (dmPFC) activity during sadness introspection when viewing sad faces was related to depression severity 1 year later and to self‐reported emotion regulation (Vilgis et al, ). We have also found that stronger activation of social–emotional processing regions (i.e., the PCC, left TPJ, and left amygdala) during sadness introspection, regardless of facial expression, moderated the relation between community crime exposure and disruptive behavior problems (Weissman et al, ). In accordance with this previous research, our first hypothesis of the present study was that engaging in sadness introspection (explicit emotion processing) would induce specific patterns of neural activity in social–emotional processing and DMN regions, including mPFC, precuneus, and temporal regions, similar to what other studies have shown.…”
Section: Introductionmentioning
confidence: 67%
“…Table shows basic demographic characteristics for both samples. Although we have previously published results from analyses using this same fMRI task completed within each sample independently, we have not conducted the same analyses reported in this paper in any of our previous publications for either sample (Vilgis et al, ; Weissman, Gelardi, et al, ; Weissman, Guyer, Ferrer, Robins, & Hastings, ).…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…As described in other work (Vilgis et al, 2018; Weissman, Gelardi, et al, 2018; Weissman, Guyer, et al, 2018), the emotional faces task (Guyer, Choate, Grimm, Pine, & Keenan, 2011) was used to examine neural responses to facial expressions of emotion while attentional focus was constrained in different ways. Participants viewed 12 sad, 12 angry, 12 happy, and 12 neutral faces portrayed by 48 unique actors.…”
Section: Methodsmentioning
confidence: 99%